Подводные археологические наблюдения и разведки у горы Опук - Зинько, В.Н.; Шамрай, А.Н. (Боспорские исследования, 2009)
The topic of localization of archaeological monuments, which have disappeared in the result of environmental change, has been raised repeatedly during the entire period of the north Pontic area archaeological science development. Outskirts of Opuk Mount on the southern coast of the Kerch Peninsula situated 50 km south-west from Kerch are of great interest. The Bosporus city of Cimmeric was situated hear in ancient time. Southern side of the mount turns its wide promontory to the south towards the sea. The promontory is of the same name as the mount. The island El’ken-Kaya is situated at the distance of 4.8 km from the promontory. As a matter of fact, the island represents four solitary rocky massifs. They are called Stone Ship Cliff group. In early 90th the authors held underwater observations not far from the shore line of Cimmeric city site. The results of archaeological prospecting near Opuk Mount make it clear that there are different types of underwater archaeological monuments in the defined area of water bordering to the mount. Their research must be continued on the basis of complex approach.